Analisis Implementasi Discovery Learning dalam Mata Pelajaran PAI pada Elemen Al-Qur’an Hadits di SDN 1 Pengadang - Abid Rahman Asrowi; Muhammad Taisir; Saparudin; Emawati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study analyzes the application of the Discovery Learning model combined with the Problem-Based Learning method in Islamic Religious Education (PAI) on the Al-Qur'an Hadith element at SDN 1 Pengadang. The objective of the study was to improve students' understanding, involvement, and internalization of Islamic values ​​in their lives. The study used a mixed approach (quantitative and qualitative) through observation, interviews, documentation, and formative assessment. The results showed that the application of Discovery Learning with Problem-Based Learning was able to improve students' activeness, motivation, and understanding. Quantitatively, the lowest score obtained by students was 50, the highest score was 77, and the average score was 67.23. Based on the classification, these results are categorized as good (61–80%). Qualitatively, students were more active in discussions, able to discover the meaning of verses and hadith, and relate them to real experiences. Obstacles faced included limited time, differences in student abilities, and a lack of supporting learning resources. However, school support in the form of teacher training, provision of facilities, and adaptive strategies were able to minimize these obstacles